A visual legacy: William Crocker's ethnographic archive. Issue 2 (4th May 2022) - Iuvaro, Fabiola
Abstract : Dr William Crocker began field research with the Canela (Maranhão state, Brazil) in 1957 and continued to do so intermittently until 2011 – a total of more than 54 years in an unprecedented long-term commitment to a field research programme in social anthropology. As soon as he arrived among the Canela, he began intensive documentation of their life. Photography and film played a major part in his observations and his use of these media proved extremely innovative in ethnographic study. Crocker produced one of the most detailed and accurate sets of visual documents about Lowland South American community life ever collected. This visual essay surveys this important ethnographic archival data (film footage, fields notes and photographs) and briefly analyses his visual enterprise, discussing the circumstances under which the images were taken, the ideas which informed them, and the general methods employed in making them. An interview I conducted with Crocker (2015) enriches our understanding of the collection.